Regular Physical Activity during Pregnancy Improves Maternal Depressive Symptoms - Abubakar, Ibrahim Ahmad (Journal of Pharmacy Practice and Community Medicine)
Dear Editor,Depressive symptoms, such as extended feeling of sadness, decreased self esteem, suicidal propensities, unconcern in activities, feelings of hopelessness and helplessness, low energy, difficulty in making decisions, sleep disorders, anxiety, petulance, and changes in eating patterns are related with an increased risk of health conditions such as osteoporosis, cardiovascular diseases, and dementia.[1] Women of childbearing age of about 22% have been estimated to have experienced depression at some point in their lives and pregnancy is a vulnerable time for depression compared with other periods of life.